2019
DOI: 10.3390/foods8120662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aroma Compounds in the Process of Wine Ageing with Oak Chips

Abstract: Many modern alcoholic beverages are subjected to ageing processes during which compounds extracted from wood contribute decisively to the overall beverage character. Wines represent a perfect example of beverage in which ageing is a crucial technological manufacturing step. During winemaking, producers accelerate chemical changes in wine composition by traditional and alternative methods, such as the use of oak wood barrels and/or oak wood chips. Our research aimed to investigate the overall volatile compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The increased presence of chemical compounds in wine aged with French oak chips generated prominent smoky, licorice and toasty aromas, whereas in wines aged with American oak chips, notes of vanilla, toasty and cacao aromas were noticed. Moreover, red wines aged with American and French oak chips were discriminated by chemometric analysis, which confirmed the evolution of AC [75]. Furthermore, contact between wood chip extracts and grape skin isolated anthocyanin extracts induced a decrease of color intensity (particularly red color), and the anthocyanin content in the different experimental synthetic wine solutions studied [76].…”
Section: Compounds Present In the Wood That Affect The Characteristicsupporting
confidence: 59%
“…The increased presence of chemical compounds in wine aged with French oak chips generated prominent smoky, licorice and toasty aromas, whereas in wines aged with American oak chips, notes of vanilla, toasty and cacao aromas were noticed. Moreover, red wines aged with American and French oak chips were discriminated by chemometric analysis, which confirmed the evolution of AC [75]. Furthermore, contact between wood chip extracts and grape skin isolated anthocyanin extracts induced a decrease of color intensity (particularly red color), and the anthocyanin content in the different experimental synthetic wine solutions studied [76].…”
Section: Compounds Present In the Wood That Affect The Characteristicsupporting
confidence: 59%
“…The botanical origin of wood has great importance in defining the transfer of aromatic compounds namely, oak lactone to wine. Wines aged in contact with American oak chips showed a significant increase of cis-oak lactone and guaiacol [31]. On the other hand, wines aged with French oak chips exhibited a major increase of furfural, 5-methylfurfural, 4-vinylguaiacol and trans-oak lactone.…”
Section: Factors Affecting Xylovolatiles Compounds During Winemakingmentioning
confidence: 92%
“…Nevertheless, other research results have shown sensory differences attributed to the origin of the oak chips [31]. The wines (Romanian red wines Fetească neagră) DOI: http://dx.doi.org /10.5772/intechopen.93529 aged in contact with American oak chips had a higher intensity of vanilla, toasty and cacao aromas compared with the wines aged using French oak chips, which had a higher intensity of smoky, licorice, and toasty aromas.…”
Section: Sensory Profile Of Wines Refined With Alternative Productsmentioning
confidence: 93%
See 2 more Smart Citations